2021
DOI: 10.1126/science.abj9184
|View full text |Cite
|
Sign up to set email alerts
|

Pol IV and RDR2: A two-RNA-polymerase machine that produces double-stranded RNA

Abstract: A tunnel between RNA polymerases Eukaryotes encode five multiple-subunit, DNA-dependent RNA polymerases, of which Pol I, Pol II, and Pol III function as single units to produce cellular single-stranded RNA. The plant-specific Pol IV forms a complex with RDR2 (an RNA-dependent RNA polymerase) to produce double-stranded precursors of small interfering RNA essential for genomic DNA methylation. Huang et al . determined the cryo–electron microscopy structures of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 68 publications
2
67
0
Order By: Relevance
“…Starting from Pol IV, RDR2 and ssDNA, the team successfully generated dsRNA products in an in vitro reaction system. Recent studies also demonstrated that Pol IV interacts directly with RDR2, forming the Pol IV–RDR2 heterodimer ( 66 , 67 ). No Pol IV homologous proteins exist in N. crassa , and the QDE-1 homodimer may mimic the Pol IV/RDR2 heterodimer in action.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from Pol IV, RDR2 and ssDNA, the team successfully generated dsRNA products in an in vitro reaction system. Recent studies also demonstrated that Pol IV interacts directly with RDR2, forming the Pol IV–RDR2 heterodimer ( 66 , 67 ). No Pol IV homologous proteins exist in N. crassa , and the QDE-1 homodimer may mimic the Pol IV/RDR2 heterodimer in action.…”
Section: Discussionmentioning
confidence: 99%
“…First of all our results demonstrated unanimously that RdRP knockdown could significantly reduce the tissue contents of short derivatives, not the full‐length derivatives, of exogenous dsRNA in A. thaliana and C. elegans . Studies have shown that RdRP is the enzyme capable of catalyzing the synthesis of RNA, siRNA and dsRNA 25,69,70 . However, no function involving dsRNA absorption and cleavage has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It was first isolated from tomato, 19 and early studies found that it functions in developmental regulation, maintenance of genome integrity and defense against foreign nucleic acids 20 . Subsequent studies found it participated in post‐transcriptional gene silence and amplified RNAi signal, secondary small interfereing (si)RNAs 21–24 and dsRNA 25 . Thus, RdRP may contribute to the long‐lasting validity period of exogenous dsRNA in plants.…”
Section: Introductionmentioning
confidence: 99%
“…RDR2 mainly associates with Pol IV to form a complex for transcribing short dsRNA precursors, which are cleaved by DCL3 to produce 24 nt siRNAs for directing DNA methylation [86][87][88][89], although RDR2 might also be able to generate 23 to 27 nt small RNAs from MIR genes to mediate DNA methylation [90]. It was reported that RDR2, Pol IV, and DCL3, core components in the RdDM pathway, mediated 24 nt vsiRNA production and played major roles against the infection of DNA viruses, such as geminiviruses [44,45].…”
Section: Production and Amplification Of Vsirnamentioning
confidence: 99%